2013
DOI: 10.1146/annurev-nucl-102912-144535
|View full text |Cite
|
Sign up to set email alerts
|

Search for Superheavy Nuclei

Abstract: We describe the discoveries of new superheavy nuclei (a) with Z = 107-112 produced in cold fusion reactions between 208 Pb and 209 Bi and beams of A > 50 and (b) with Z = 113-118 in hot fusion reactions between actinide nuclei and 48 Ca. We also discuss the facilities used in these measurements. We compare the behavior of the α-decay energies and half-lives, spontaneous fission half-lives, cross sections, and excitation functions with expectations from theoretical calculations. Finally, we outline future resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
180
0
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 237 publications
(185 citation statements)
references
References 97 publications
2
180
0
3
Order By: Relevance
“…For seven of those, alpha decay to 262 Db had an average 8.67 MeV energy and for four cases the chains continued to the 4.1 s alpha decay of 258 Lr [15] with an average energy of 8.67 MeV all with excellent internal agreement and with the 2006 study of Qin et al [12]. These agree with the [6].) The colors indicate different decay modes for nuclide Z/A along with its half-life in milliseconds (ms), seconds (s), minutes (m) or hours (h) following the convention and data in [6] 113.…”
Section: Z = 113supporting
confidence: 84%
See 2 more Smart Citations
“…For seven of those, alpha decay to 262 Db had an average 8.67 MeV energy and for four cases the chains continued to the 4.1 s alpha decay of 258 Lr [15] with an average energy of 8.67 MeV all with excellent internal agreement and with the 2006 study of Qin et al [12]. These agree with the [6].) The colors indicate different decay modes for nuclide Z/A along with its half-life in milliseconds (ms), seconds (s), minutes (m) or hours (h) following the convention and data in [6] 113.…”
Section: Z = 113supporting
confidence: 84%
“…These agree with the [6].) The colors indicate different decay modes for nuclide Z/A along with its half-life in milliseconds (ms), seconds (s), minutes (m) or hours (h) following the convention and data in [6] 113. The properties of all three chains are reproduced in Fig.…”
Section: Z = 113supporting
confidence: 74%
See 1 more Smart Citation
“…A 2004 collaboration of Oganessian et al [10] reported the observation of one complete alpha-decay chain assigned to the [7].) The colors indicate different decay modes for nuclide Z/A along with its half life in milliseconds (ms), seconds (s), minutes (m) or hours (h) following the convention and data of [7], q.v.…”
Section: Discovery Profilesmentioning
confidence: 99%
“…The use of cold fusion reactions enabled the discovery of six new elements, from bohrium (Z=107) to nihonium (Z=113) [8] and the use of hot fusion reactions led to the discovery of elements up to oganesson (Z=118) [8].…”
Section: Introductionmentioning
confidence: 99%